Cyclin B1 Overexpression Induces Cell Death Independent of Mitotic Arrest - Eichhorn, Joshua M. (PLoS One, 2014)
Microtubule inhibitors are widely used in cancer chemotherapy. These drugs characteristically induce mitotic arrest and cell death but the mechanisms linking the two are not firmly established. One of the problems is that cancer cells vary widely in their sensitivity to these agents, and thus comparison of data from different systems is difficult. To alleviate this problem we sought to molecularly induce mitotic death and study its mechanisms, by expressing non-degradable cyclin B (R42A) in HeLa cells. However, this approach failed to induce significant mitotic arrest, Cdk1 activation, or phosphorylation of anti-apoptotic Bcl-2 proteins, all characteristics of cells treated with microtubule inhibitors. Furthermore, cyclin B1-R42A induced rapid cell death, and when expressed in synchronized cells, cell death occurred in G1 phase. Decreasing the plasmid concentration reduced transfection efficiency but restored mitotic arrest and eliminated non-specific death. These results show that inappropriate overexpression of cyclin B1 causes non-specific cell death and suggest caution in its use for the study of mitotic events.